2020
DOI: 10.1136/jnnp-2020-323826
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between plasma and cerebrospinal fluid biomarkers for the early diagnosis and association with survival in prion disease

Abstract: ObjectiveTo compare the diagnostic accuracy and the prognostic value of blood and cerebrospinal fluid (CSF) tests across prion disease subtypes.MethodsWe used a single-molecule immunoassay to measure tau and neurofilament light chain (NfL) protein levels in the plasma and assessed CSF total(t)-tau, NfL and protein 14-3-3 levels in patients with prion disease (n=336), non-prion rapidly progressive dementias (n=106) and non-neurodegenerative controls (n=37). We then evaluated each plasma and CSF marker for diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 32 publications
3
75
2
Order By: Relevance
“…However, in contrast to the CSF analyte, blood NfL levels did not significantly differ among the most prevalent sCJD subtypes (Kovacs et al, 2017;Thompson et al, 2018;Abu-Rumeileh et al, 2020a). Interestingly, sCJD VV2, typically characterized by the highest CSF NfL and t-tau values among sCJD subtypes (Lattanzio et al, 2017;Abu-Rumeileh et al, 2018b, showed similar blood NfL and reduced blood tau levels compared with the MM(V)1 type (Kovacs et al, 2017;Abu-Rumeileh et al, 2020a). These data suggest that the different regional lesion profiles between the two CJD subtypes (Parchi et al, 1999;Baiardi et al, 2017), particularly the early cortical neuronal damage featuring MM(V)1 but not VV2, might be responsible for a higher spill over of these molecules in the blood compared to other brain regions (Abu-Rumeileh et al, 2020a).…”
Section: Diagnostic Value and Distribution Across Prion Disease Subtypesmentioning
confidence: 70%
See 4 more Smart Citations
“…However, in contrast to the CSF analyte, blood NfL levels did not significantly differ among the most prevalent sCJD subtypes (Kovacs et al, 2017;Thompson et al, 2018;Abu-Rumeileh et al, 2020a). Interestingly, sCJD VV2, typically characterized by the highest CSF NfL and t-tau values among sCJD subtypes (Lattanzio et al, 2017;Abu-Rumeileh et al, 2018b, showed similar blood NfL and reduced blood tau levels compared with the MM(V)1 type (Kovacs et al, 2017;Abu-Rumeileh et al, 2020a). These data suggest that the different regional lesion profiles between the two CJD subtypes (Parchi et al, 1999;Baiardi et al, 2017), particularly the early cortical neuronal damage featuring MM(V)1 but not VV2, might be responsible for a higher spill over of these molecules in the blood compared to other brain regions (Abu-Rumeileh et al, 2020a).…”
Section: Diagnostic Value and Distribution Across Prion Disease Subtypesmentioning
confidence: 70%
“…More recently, blood NfL levels were also found significantly higher in patients with prion disease belonging to all CJD forms and subtypes than both controls and other NDs ( Table 1; Steinacker et al, 2016;Kovacs et al, 2017;Thompson et al, 2018Thompson et al, , 2020Abu-Rumeileh et al, 2020a). However, in contrast to the CSF analyte, blood NfL levels did not significantly differ among the most prevalent sCJD subtypes (Kovacs et al, 2017;Thompson et al, 2018;Abu-Rumeileh et al, 2020a).…”
Section: Diagnostic Value and Distribution Across Prion Disease Subtypesmentioning
confidence: 88%
See 3 more Smart Citations